2016
DOI: 10.1136/jclinpath-2016-203619
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of lung adenocarcinoma in situ and minimally invasive adenocarcinoma from intraoperative frozen sections: an analysis of 136 cases

Abstract: Diagnosis of AIS and MIA from intraoperative frozen sections is feasible. We provide several modifications that may improve the diagnostic accuracy of intraoperative frozen sections for early-stage lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
(11 reference statements)
2
35
1
Order By: Relevance
“…Currently, the intraoperative pathological classification of early lung adenocarcinoma is mainly obtained by FS. One study [12] analyzed 136 patients with early lung adenocarcinoma, and found that the concordance rate between FS and paraffin sections was only 63.24 %, finding that FS gave a deferral diagnosis(could only provide a diagnosis of adenocarcinoma, where the pathological classification was unclear) in approximately 32.35 % of all cases. In an analysis [14] of 224 consecutive primary pulmonary adenocarcinomas, the FS errors and deferrals were identified in 12.1 % and 6.3 % of the cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the intraoperative pathological classification of early lung adenocarcinoma is mainly obtained by FS. One study [12] analyzed 136 patients with early lung adenocarcinoma, and found that the concordance rate between FS and paraffin sections was only 63.24 %, finding that FS gave a deferral diagnosis(could only provide a diagnosis of adenocarcinoma, where the pathological classification was unclear) in approximately 32.35 % of all cases. In an analysis [14] of 224 consecutive primary pulmonary adenocarcinomas, the FS errors and deferrals were identified in 12.1 % and 6.3 % of the cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These results proved that the diagnostic performance of our radiomics method is not inferior to frozen sections. In the studies conducted by He P et al and Walts AE et al [12,14], the FS deferrals were identified as 32.35 % and 6.3 % of all the cases, respectively, which would lead to inappropriate surgical treatment, the introduction of a new method to solve this problem is necessary. Therefore, it is meaningful that radiomics serve as a reliable complementary method for the pathological classification of the cases where FS can't give timely diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, tumor size had a significant influence on the concordance rate. Another retrospective study from China reported that the concordance rate in diagnosis of AIS and MIA was 95.6% among 136 patients with AIS or MIA ≤3 cm . Of note, further histologic subtyping including detection of high grade histology on frozen section was not attempted in both studies.…”
Section: Introductionmentioning
confidence: 99%
“…In one series, other features that caused diagnostic challenges included lack of cytologic atypia and the presence of fibrosis or inflammation. 22 However, in experienced centers, accuracy rates are high even for adenocarcinoma in situ and minimally invasive adenocarcinoma, 23 despite these caveats. Nevertheless, it is difficult to uniformly recommend definitive assessment by frozen section alone, but rather a clinical and radiologic comparison with frozen section during intraoperative consultation seems a more rational approach to mitigate the effect of sampling.…”
Section: Diagnosis Of Adenocarcinoma In Situ Andmentioning
confidence: 99%